2010 Integrated Communications, Navigation, and Surveillance Conference Proceedings 2010
DOI: 10.1109/icnsurv.2010.5503242
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stakeholder benefits of NextGen Trajectory-Based Operations

Abstract: Abstract-Trajectory-Based Operations is a NextGen initiative that seeks to increase the effective-capacity of the National Airspace System by adding flexibility to the 4-D trajectories as flights traverse airspace. More flexible trajectories can minimize the airlines operating costs (i.e., distance flown), shift the geography of Air Traffic Control (ATC) workload (i.e., sectors used), shift the time-intensity of ATC workload (i.e., flights counts per sector), and reduce congestion in the destination airports.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Furthermore, due to the high degrees of freedom available in flight plan route selection and the varying constraints in the NAS, flight plan route selection can contribute to the stochasticity and performance of the NAS [2]. In the past efforts have been made to analyze benefits direct routing and free flights [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, due to the high degrees of freedom available in flight plan route selection and the varying constraints in the NAS, flight plan route selection can contribute to the stochasticity and performance of the NAS [2]. In the past efforts have been made to analyze benefits direct routing and free flights [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment 2 results in the wider range of improvement (up to 2.2 million gallons). In the absence of weather effects (e.g., no wind) saving of fuel can only come from selecting shorter paths to fly as shown in previous studies [12] [13]. Studying the routes selected by the airlines shows that the shortest path, i.e., the Great Circle Distance path between origin and destination, is one of the most frequently selected routes.…”
Section: Results For the Airlinesmentioning
confidence: 78%
“…Route selection is of little help for this metric under this level of demand. Previous studies with similar levels of demand [12] [13] showed that airlines selecting shorter paths reduce their delays and the total number of conflicts in the system as well as their fuel-burn, but not the congestion at destination airports.…”
Section: Results For the Airlinesmentioning
confidence: 94%
“…Currently, aircraft do not normally fly great circle routes because of sector route structures, and they may also be subject to delay – e.g., stacking because of airport capacity limits. The excess distances flown by aircraft have been the subject of considerable research interest, e.g., Magill (1998) and Calderon-Meza and Sherry (2010) for European and USA flights respectively. Fuel's contribution to the total costs incurred obviously varies with the relative price of jet kerosene compared to other operational costs.…”
Section: Fuel Efficiency Killer Appsmentioning
confidence: 99%